Patients’ reactions to digital rectal examination of the prostate - Udoh EA; Peter OO (Ibom Medical Journal, 2022)
Background: Digital rectal examination (DRE) of the prostate is a simple, fast, cost effective and safe procedure, however, because of previous painful experience, some men may refuse it. Other negative factors include cultural barriers, fear of discovering cancer and embarrassments. However, some men accept DRE because of their symptoms and wishes to contribute to science. The aim of this study was to examine how previous experience of DRE could influence a repeat and to further evaluate their impression before and after DRE including pain score. Patients and Methods: We evaluated one hundred patients who met the inclusion criteria using a structured questionnaire that detailed information on patients biodata, their previous DRE experiences, expectations before and reactions after a repeat. Pain score was also examined using visual analog scale of 0 to 10. Data were collated and analysed using statistical package for social sciences (SPSS) version 20.0. P-value was set at <0.05. Results: Mean age of patients was 64.88±7.53 years ranging from 46 to 82 years. Forty five percent of them complained of pain from previous DRE while 55% reported no pain. Forty one percent of the men anticipated pain before this present procedure but only 8% of them reported that it was painful and humiliating after the procedure. Fifty nine percent had good impression before DRE and after the procedure 92% reported good impression. All patients expressed their willingness to repeat DRE in future if need be and to encourage friends who may need DRE evaluation of their condition. Mean pain score was 0.59 ± 1.349 (0 – 9). Conclusion: Patients previous experience of DRE could negatively influence a repeat procedure because of pain, improper counseling apart from some cultural barriers. DRE in the hands of Urologists has been better tolerated than other clinicians. This calls for proper exposure of medical students to this procedure and need for continuous medical education for other clinicians for skills improvement.